Perceived quality, authenticity, and price in tourists' dining experiences: Testing competing models of satisfaction and behavioral intentions. (October 2019) - Muskat, Birgit; Hörtnagl, Tanja; Prayag, Girish; Wagner, Sarah
This study examines tourists' dining experiences and tests competing models of predictors of satisfaction and behavioral intentions. Specifically, we examine the influence of service quality, quality of environment, food quality, price fairness, authenticity, and tourist satisfaction on behavioral intentions. Within the context of mountain hut casual ethnic restaurants and a survey of 304 respondent tourists, we apply partial least squares-structural equation modeling (PLS-SEM) to test both the baseline and the competing, hierarchical latent model. First, results for the baseline model show that satisfaction fully mediates the relationship between the various quality attributes and behavioral intentions. Second, results from the competing model confirm that food quality, service quality, and quality of environment form a second-order construct of perceived quality. Third, results reveal that service quality, quality of the environment, and food quality are best represented as a second-order construct in modeling predictors to evaluate the tourism dining experiences relative to tourist satisfaction and behavioral intentions. Fourth, we show that authenticity is a stronger predictor of satisfaction than price fairness and service quality.